Corporate Social Responsibility in the context of diffusionof new technologies in modern economy - Zinczuk, Bartłomiej (Społeczna odpowiedzialność biznesu w kontekście dyfuzji nowych technologii we współczesnej gospodarce, 2018)
The main goal of the article is to present the scope and diversity of pro-environmental information reporting in the five largest banks in Poland according to the balance sheet total at the end of 2016. Non-financial reports of the largest banks have been analysed over the last two financial years, 2015–2016. The publication presents formal and legal requirements (Directive 2014/95 EU, Article 49 of the Accounting Act, National Accounting Standard No. 9), which determines the necessity of reporting such information by public interest entities, such as modern banks. Attention was also given to the way environmental information is reported in the above-mentioned banks (with particular reference to the GRI standard). The methods employed during the preparation of the publication include: critical analysis of the literature, including domestic and foreign publications in the area of corporate social responsibility, and the analysis of non-financial reports of the largest Polish banks
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2018; Nr 520; s. 151-157
Keywords: corporate social responsibility; non-financial reporting; bank; environmental responsibility; CSR; odpowiedzialność środowiskowa; raportowanie niefinansowe